2011
DOI: 10.5380/avs.v16i3.19509
|View full text |Cite
|
Sign up to set email alerts
|

PARÂMETROS ELETROCARDIOGRÁFICOS DE CASCAVÉIS (Crotalus durissus, Linnaeus, 1758) EM CATIVEIRO.

Abstract: Endereço para correspondência: Daniel Rodrigues Stuginski: dstuginski@yahoo.com.br RESUMO: Apesar de a eletrocardiografia ser vastamente empregada na clínica veterinária, esta ferramenta ainda é pouco utilizada no diagnóstico de patologias em serpentes. Este trabalho teve como objetivo a caracterização dos parâmetros eletrocardiográficos da cascavel Crotalus durissus em cativeiro, sob condições controladas. Para isto, 23 serpentes foram submetidas ao exame eletrocardiográfico, aonde os seguintes parâmetros for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Valentinuzzi et al, (1970) observed considerable variation in the T wave amplitude and duration over several days in snakes, although no immediate apparent cause of such variations was identified. The values for the ECG parameters in P. guttatus were lower than those for other species such as Boa constrictor (Conceição et al, 2014;Armelin et al 2019), Lampropeltis getuhts (Valentinuzzi et al, 1970) and Eunectes murinus (Strussmann, and Sazima,1991), but similar to those reported for Spilotes pullatus (Cruz and Junkes, 2008) and Crotalus durissus (Stuginski et al, 2011).…”
supporting
confidence: 71%
See 2 more Smart Citations
“…Valentinuzzi et al, (1970) observed considerable variation in the T wave amplitude and duration over several days in snakes, although no immediate apparent cause of such variations was identified. The values for the ECG parameters in P. guttatus were lower than those for other species such as Boa constrictor (Conceição et al, 2014;Armelin et al 2019), Lampropeltis getuhts (Valentinuzzi et al, 1970) and Eunectes murinus (Strussmann, and Sazima,1991), but similar to those reported for Spilotes pullatus (Cruz and Junkes, 2008) and Crotalus durissus (Stuginski et al, 2011).…”
supporting
confidence: 71%
“…To record the ECG, the snakes were restrained individually with the ventral surface downwards in a clear plastic tube, with the cephalic one-third to half of the body inserted into the tube (Figure 1). Most work on heart rate in snakes is carried out under resting conditions and with anesthetized animals, a factor that can interfere with a full understanding of this animals (Lilywhite et al, 1999;Stunginsk;Fernandes;Grego, 2011). The ECG was recorded and analyzed using a computerized electrocardiograph with appropriate acquisition software (ECG PCV Acquisition Module 6.2, Tecnologia Eletrônica Brasileira -TEB, São Paulo, SP, Brazil).…”
Section: Signal Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to RASKE et al (2012), safe and inexpensive measurements of heart rate may be valuable for exotic animal medicine. STUGINSKI et al (2011) also found no relationship between HR and sex in Crotalus durissus Linnaeus, 1758. Sexual changes in the HR of snakes may occur due to pregnancy, which increases heart rate (BIRCHARD et al 1984).…”
Section: Short Communicationmentioning
confidence: 99%
“…However, it was difficult to perform in large snakes with strong muscles and a deep body cavity. The manual method is valuable when it is not possible to use more sophisticated methods such as electrocardiogram (e.g., VALENTINUZII et al 1969a, b, RUTSKINA et al 2009, STUGINSKI et al 2011, Doppler blood flow detector Figure 1. Relationship between body mass (g) and log 10 -transformed heart rate, measured as beats per minute in 30 individuals of Boa constrictor from Núcleo Regional de Ofiologia da Universidade Federal do Ceará.…”
Section: Short Communicationmentioning
confidence: 99%